2017
DOI: 10.1159/000461483
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose Induces Mouse Mesangial Cell Overproliferation via Inhibition of Hydrogen Sulfide Synthesis in a TLR-4-Dependent Manner

Abstract: Background/Aims: Overproliferation of mesangial cells was believed to play an important role in the progress of diabetic nephropathy, one of the primary complications of diabetes. Hydrogen sulfide (H2S), a well-known and pungent gas with the distinctive smell of rotten eggs, was discovered to play a protective role in diabetic nephropathy. Methods: MTT assay was used to examine the viability of mesangial cells. Small interfering RNA was used to knock down the expression of TLR4 while specific inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 53 publications
(44 reference statements)
2
16
0
Order By: Relevance
“…In fact, H 2 S donors are able to reduce the infiltration of neutrophils and lymphocytes in several models and reduce the expression of many pro‐inflammatory cytokines, most likely related to its ability to suppress the activation of NF‐κB, a factor regulated by TLR2/TLR4 signaling . In addition, H 2 S supplementation inhibited TLR4 expression in a mouse model of mesangial cell overproliferation induced by high glucose . These evidences suggest that H 2 S is able to regulate TLR expression, although this regulation seems to be specific for the different tissues, species or models used.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In fact, H 2 S donors are able to reduce the infiltration of neutrophils and lymphocytes in several models and reduce the expression of many pro‐inflammatory cytokines, most likely related to its ability to suppress the activation of NF‐κB, a factor regulated by TLR2/TLR4 signaling . In addition, H 2 S supplementation inhibited TLR4 expression in a mouse model of mesangial cell overproliferation induced by high glucose . These evidences suggest that H 2 S is able to regulate TLR expression, although this regulation seems to be specific for the different tissues, species or models used.…”
Section: Discussionmentioning
confidence: 98%
“…31 In addition, H 2 S supplementation inhibited TLR4 expression in a mouse model of mesangial cell overproliferation induced by high glucose. 32 These evidences suggest that H 2 S is able to regulate TLR expression, although this regulation seems to be specific for the different tissues, species or models used.…”
Section: Previous Studies Have Shown Interactions Between H 2 S and Tlr4mentioning
confidence: 99%
“…It also raises the possibility of the use of NaHS as a potential therapeutic agent for high glucose-induced ADAM17 expression and sFlt-1 production. Although the inhibition effect of high glucose on H 2 S production has been demonstrated in several different types of cells [15, 27, 28], the mechanisms responsible for high glucose on H 2 S synthase remain unclear. It has been reported that high glucose inhibited H 2 S production via TLR4 inflammatory pathway in mouse mesangial cells [28].…”
Section: Discussionmentioning
confidence: 99%
“…Although the inhibition effect of high glucose on H 2 S production has been demonstrated in several different types of cells [15, 27, 28], the mechanisms responsible for high glucose on H 2 S synthase remain unclear. It has been reported that high glucose inhibited H 2 S production via TLR4 inflammatory pathway in mouse mesangial cells [28]. In addition, the expression of several microRNAs, including miR-192 [29], miR-204 [30], and miR-217 [31], was upregulated by high glucose.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism underlying the pathogenesis of DN is incompletely resolved, and there is no specific drug for the treatment and prevention of the development of DN, which has become a worldwide burden on public health. Recently, dysfunction of glomerular mesangial cells has been suggested to play a vital role in the pathogenesis of DN [3]_ENREF_3. Actually, even with strict control of plasma glucose, many diabetic patients eventually develop DN.…”
Section: Introductionmentioning
confidence: 99%